Angiotensin-Converting Enzyme Gene I/D Polymorphism Is Associated With Systemic Lupus Erythematosus Susceptibility: An Updated Meta-Analysis and Trial Sequential Analysis - Khan, Saif; Dar, Sajad A.; Mandal, Raju K.; Jawed, Arshad; Wahid, Mohd; Panda, Aditya K.; Lohani, Mohtashim; Mishra, B. N.; Akhter, Naseem; Haque, Shafiul (Frontiers in Physiology, 2018)
Angiotensin-converting enzyme (ACE) gene is indispensable for endothelial control and vascular tone regulatory systems, usually affected in Systemic Lupus Erythematosus (SLE). ACE insertion/deletion (I/D) polymorphism may influence the progress of SLE. Earlier studies have investigated this association without any consistency in results. We performed this meta-analysis to evaluate the precise association between ACE I/D polymorphism and SLE susceptibility. The relevant studies were searched until December, 2017 using Medline (PubMed), Google-Scholar and EMBASE search engines. Twenty-five published studies involving 3308 cases and 4235 controls were included in this meta-analysis. Statistically signiﬁcant increased risk was found for allelic (D vs I: p=0.007; OR=1.202, 95% CI=1.052 to 1.374), homozygous (DD vs II: p=0.025; OR=1.347, 95% CI=1.038 to 1.748), dominant (DD+ID vs II: p=0.002; OR=1.195, 95% CI=1.070 to 1.334), and recessive (DD vs ID+II: p=0.023; OR=1.338, 95% CI=1.042 to 1.718) genetic models. Subgroup analysis stratiﬁed by Asian ethnicity revealed significant risk of SLE in allelic (D vs I: p=0.045; OR=1.238, 95% CI=1.005 to 1.525) and marginal risk in dominant (DD+ID vs II: p=0.056; OR=1.192, 95% CI=0.995 to 1.428) models; whereas, no association was observed for Caucasian and African population. Publication bias was absent. In conclusion, ACE I/D polymorphism has significant role in overall SLE risk and it can be exploited as a prognostic marker for early SLE predisposition.